1992
DOI: 10.1007/bf00184648
|View full text |Cite
|
Sign up to set email alerts
|

Increased cotinine elimination and cotinine-N-oxide formation by phenobarbital induction in rat and mouse

Abstract: The metabolic fate of cotinine, the major metabolite of nicotine, was studied in phenobarbital-induced and non-induced isolated perfused rat lung and liver and in isolated hepatocytes of rats and mice. The non-induced lung tissue showed low cotinine metabolizing capacity while the perfused liver was approximately four times more active. After phenobarbital pretreatment the metabolism of cotinine was increased eight-fold in the intact liver. A substantial increase in cotinine metabolism was also found in isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Additional studies using CYP450 inhibitors demonstrated that COX is formed from COT in hamster and guinea pig liver microsomes, potentially by CYP450 enzymes (Jenner et al, 1971). This was validated in further studies where phenobarbital (a strong CYP450 inducer) pretreatment in rat liver increased COX production by 8-fold, an effect that was negated when co-treated with the CYP450 inhibitor, metyrapone (Foth et al, 1992). The goal of the present study was to identify the human CYP450 enzymes responsible for COX formation and to determine whether genetic variations in these enzymes affect the levels of COX formation in a panel of human liver specimens.…”
Section: Introductionmentioning
confidence: 72%
“…Additional studies using CYP450 inhibitors demonstrated that COX is formed from COT in hamster and guinea pig liver microsomes, potentially by CYP450 enzymes (Jenner et al, 1971). This was validated in further studies where phenobarbital (a strong CYP450 inducer) pretreatment in rat liver increased COX production by 8-fold, an effect that was negated when co-treated with the CYP450 inhibitor, metyrapone (Foth et al, 1992). The goal of the present study was to identify the human CYP450 enzymes responsible for COX formation and to determine whether genetic variations in these enzymes affect the levels of COX formation in a panel of human liver specimens.…”
Section: Introductionmentioning
confidence: 72%
“…3). Previous studies had identified 5-HC and CNO in vitro upon incubation of (a) recombinant human CYP2A6 with hamster liver microsome and cotinine (Murphy et al, 1999) and (b) primary mouse hepatocyte culture with 14 C-cotinine (Foth et al, 1992) respectively. CNO was quantified in the plasma of rats (Li et al, 2012), in which oxidation of cotinine to CNO is catalyzed by CYP2B1, (Hammond et al, 1991, Nakayama et al, 1993, an enzyme that shows less similarity to human CYP2A6 than mouse CYP2A5.…”
Section: Discussionmentioning
confidence: 99%
“…DMD Fast Forward. Published on October 2, 2022 as DOI: 10.1124/dmd.122.001059 at ASPET Journals on October 9, 2022 dmd.aspetjournals.org Downloaded from liver microsome and cotinine (Murphy et al, 1999), and CNO upon incubation of primary mouse hepatocyte culture with 14 C-cotinine (Foth et al, 1992). However, 5-HC and CNO have not been detected in vivo in the plasma of mice after nicotine administration.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a cytochrome P450 pathway, the in vivo conversion of cotinine to trans-3hydroxycotinine is accompanied by an apparent deuterium isotope effect of 8 (Dagne et al, 1974). A recent study on enzyme induction employing perfused organs and whole cell preparations does not report trans-3-hydroxycotinine as a cotinine or nicotine metabolite (Foth et al, 1992). A recent study on enzyme induction employing perfused organs and whole cell preparations does not report trans-3-hydroxycotinine as a cotinine or nicotine metabolite (Foth et al, 1992).…”
Section: ~-Nicotyrine 133mentioning
confidence: 97%
“…Although some debate continues to appear in the literature Benowitz and Jacob, 1991;Kyerematen et al, 1991a), the majority of quantitative studies indicates that 11 is the principal metabolite excreted in the urine of humans and experimental animals administered nicotine (Foth et al, 1992;Neurath et al, 1987;Voncken et al, 1989;O'Doherty et al, 1988;Cundy and Crooks, 1987;Kyerematen and Vesell, 1991b). A careful analysis of human urine using synthetic standards of both the cis-(12) and trans-isomers failed to detect significant levels of the cis isomer .…”
Section: ~H Qo:~~6hhgosmentioning
confidence: 99%